The Role of Interleukin-18 in the Development and Progression of Atherosclerosis - Bahrami, Afsane; Sathyapalan, Thozhukat; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2021)
Atherosclerosis (AS), as a chronic inflammatory disorder of the cardiovascular system, is one of the leading causes of ischemic heart disease, stroke and peripheral vascular disease. There is growing evidence on the role of innate and adaptive immunity in the pathogenesis of atherosclerosis. Interleukin-18 is one of the novel proinflammatory cytokines involved in atherogenesis, atherosclerotic plaque instability and plaque rupture. In this review, we overview the findings of preclinical and clinical studies about the role and mechanism of action of IL-18 in the pathogenesis of AS, which could offer novel prognostic and therapeutic approaches.
Keywords: polymorphism